Contribution Percentage of Some Physical and Motor Abilities and The Speed and Accuracy of All Types of Volleyball Serves - Sabhan, Hussein (Journal of Physical Education, 2013)
Serving in all of its types is considered the most important skill in volleyball because it needs the best position to execute the skill accurately. It is also the first and fastest means for gaining a point compared to the other skills. This skill requires motor skills like speed of motor response, motor accuracy, agility and flexibility as well as directing the balls into an accurate position. These abilities require specific training styles due to their great effect on game results. The importance of the research lies in identifying the contribution percentage of some physical and motor abilities and the speed and accuracy of performing all types of volleyball serve. The aim of the research is to identify contribution percentage of some physical and motor abilities and the speed and accuracy of performing all types of volleyball serve. The hypothesis of the research is that there is a contribution percentage of some physical and motor abilities and the speed and accuracy of performing all types of volleyball serve. The researchers used the descriptive method. The subjects were (16) Iraqi volleyball league players aged 18 - 28 years old. The researcher came up with many conclusions like there are differences in contribution percentage of motor abilities in speed and accuracy of performing all types of volleyball serve. In addition to that, there is a contribution relation between motor abilities and speed and accuracy of serve. Finally, the researchers recommended the necessity of specifying enough time for training arms explosive power during the training session as well as endurance, flexibility, agility, transitional speed and muscular strength balance. At the end, they recommended paying attention training to speed and accuracy of all types of volleyball serve